Description of Behavior and Attitudes of Postpartum Mothers in Implementing Locally Culturally-Based Self-Care in Bandar Baru Village, Sibolangit Sub-District - Aspiati Aspiati; Ristika Julianty Singarimbun (Journal of Innovative and Creativity (Joecy), 2024)
Background. The postpartum period represents a critical phase of physical and psychological recovery for mothers following childbirth. In many rural communities in North Sumatra, Indonesia, local cultural practices continue to shape the manner in which postpartum care is implemented, yet the extent to which these practices are consistent with evidence-based midwifery standards remains inadequately examined. Objective. This study aimed to describe the behavior and attitudes of postpartum mothers regarding locally culturally-based self-care practices in Bandar Baru Village, Sibolangit Sub-District, Deli Serdang Regency, North Sumatra. Methods. A descriptive quantitative study with a cross-sectional approach was conducted from October 18, 2024 to January 31, 2025. The total sampling technique was used, encompassing 52 postpartum mothers who met the inclusion criteria. Data were collected using a validated structured questionnaire measuring self-care behavior and attitude. Univariate analysis was performed to generate frequency distributions and percentages. Ethical clearance was obtained from the Research Ethics Committee of STIKes Darmo, with reference number 012/KEPK-STIKESDARMO/X/2024. Results. The majority of respondents (71.2%) were aged 20–35 years, with secondary education (53.8%) being most prevalent. In terms of self-care behavior, 55.8% of postpartum mothers demonstrated adequate behavior, while 44.2% showed inadequate behavior. Regarding attitude, 61.5% of respondents held a positive attitude toward self-care, while 38.5% demonstrated a negative attitude. Locally culturally-based practices identified included consumption of traditional herbal beverages (jamu) (80.8%), application of traditional abdominal binders (gurita) (75.0%), dietary taboos (67.3%), traditional massage (57.7%), and restricted physical activity (65.4%). Conclusion. There remains a substantial proportion of postpartum mothers with inadequate self-care behavior, despite the prevalence of positive attitudes. Culturally-rooted practices continue to exert a strong influence on postpartum care. Healthcare providers, particularly midwives, should integrate cultural competence into postpartum counseling to harmonize local wisdom with clinical evidence.